Increased lean mass with reduced fat mass in an elite female cyclist returning to competition: case study - Haakonssen, E. C.; Martin, D. T.; Burke, L. M.; Jenkins, D. G. (International Journal of Sports Physiology and Performance, 2013)
Body composition in a female road cyclist was measured using dual-energy X-ray absorptiometry (5 occasions) and anthropometry (10 occasions) at the start of the season (Dec to Mar), during a period of chronic fatigue associated with poor weight management (Jun to Aug), and in the following months of recovery and retraining (Aug to Nov). Dietary manipulation involved a modest reduction in energy availability to 30-40 kcal /kg fat-free mass·d and an increased intake of high-quality protein, particularly after training (20 g). Through the retraining period, total body mass decreased (-2.82 kg), lean mass increased (+0.88 kg), and fat mass decreased (-3.47 kg). Hemoglobin mass increased by 58.7 g (8.4%). Maximal aerobic- and anaerobic- power outputs were returned to within 2% of preseason values. The presented case shows that through a subtle energy restriction associated with increased protein intake and sufficient energy intake during training, fat mass can be reduced with simultaneous increases in lean mass, performance gains, and improved health.